2018
DOI: 10.1186/s12913-018-3219-2
|View full text |Cite
|
Sign up to set email alerts
|

Children and young people’s participation in developing interventions in health and well-being: a scoping review

Abstract: BackgroundGreater interest is being shown in participatory approaches, especially in research on interventions that concern children and young people’s health and well-being. Although participatory approaches have user involvement in common, they differ in terms of the explicit guidance on how to actually involve and engage children and young people in health research. The aim of this scoping review was to systematically map recent research involving children and young people in the development of intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(144 citation statements)
references
References 76 publications
10
109
0
1
Order By: Relevance
“…Furthermore, the nature of the students' involvement in the design of VR FestLab ensured a high level of influence on the design and production tasks, which increased students' self-efficacy. This corresponds with several studies that argued that participatory research can empower participants to influence and generate novel ideas that will improve the creation of health products and services as well as their implementation in practice [4,17,27]. Empowerment became evident in this Living Lab process, where game design students took initiative and delivered the new mini-game components further enhancing the VR FestLab product.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the nature of the students' involvement in the design of VR FestLab ensured a high level of influence on the design and production tasks, which increased students' self-efficacy. This corresponds with several studies that argued that participatory research can empower participants to influence and generate novel ideas that will improve the creation of health products and services as well as their implementation in practice [4,17,27]. Empowerment became evident in this Living Lab process, where game design students took initiative and delivered the new mini-game components further enhancing the VR FestLab product.…”
Section: Discussionsupporting
confidence: 75%
“…Participatory research often strives to increase the likelihood of developing more effective and efficient interventions that more precisely address health and well-being issues among the target group [27]. Studies have shown improvements in products developed in a co-creation process, especially on implementation and usability of the product or service [1].…”
Section: Discussionmentioning
confidence: 99%
“…In order to grade the level of participation in the analysis, the data were categorized in accordance with Shier's Pathways to Participation Model. 19 A participatory design was used 20 which in this study included four phases conducted in succession to each other. Those phases are outlined below and shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Limitations of the study should be considered, such as the small sample size, which makes it difficult to generalize the findings. However, one of the strengths of the present study was that children with and without disabilities were included as co-designers, 20 supported by both parents and radiographers. There is evidence that involving end-users (in this study the children, their families and radiographers) facilitates improving the dissemination of research findings within the community (Cooperative Research Centre for Living with Autism, 2016).…”
Section: Subcategory Categorymentioning
confidence: 99%
“…While there is no consensus on one definition for public and patient involvement (PPI) nor in relation to the terminology used (e.g engagement and involvement are often used interchangeably or with different connotations), there is a growing abundance of academic and grey literature on the merits, impact and experiences of PPI in health and social care research . In the UK, the National Institute for Health Research (NIHR) has set up the platform INVOLVE to promote and share best practices for PPI.…”
Section: Introductionmentioning
confidence: 99%